2016
DOI: 10.1016/s2214-109x(16)30096-1
|View full text |Cite
|
Sign up to set email alerts
|

Daily co-trimoxazole prophylaxis to prevent mortality in children with complicated severe acute malnutrition: a multicentre, double-blind, randomised placebo-controlled trial

Abstract: SummaryBackgroundChildren with complicated severe acute malnutrition (SAM) have a greatly increased risk of mortality from infections while in hospital and after discharge. In HIV-infected children, mortality and admission to hospital are prevented by daily co-trimoxazole prophylaxis, despite locally reported bacterial resistance to co-trimoxazole. We aimed to assess the efficacy of daily co-trimoxazole prophylaxis on survival in children without HIV being treated for complicated SAM.MethodsWe did a multicentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
173
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 126 publications
(185 citation statements)
references
References 32 publications
11
173
0
1
Order By: Relevance
“…Children with cSAM were actively linked to therapeutic and supplementary feeding programmes upon hospital discharge. Missing follow‐up visits and needing to be traced by a fieldworker making a home visit was associated with readmission (with any condition, not just complicated SAM) and death, as previously published (Berkley et al, ; Ngari et al, a).…”
Section: Methodssupporting
confidence: 69%
See 3 more Smart Citations
“…Children with cSAM were actively linked to therapeutic and supplementary feeding programmes upon hospital discharge. Missing follow‐up visits and needing to be traced by a fieldworker making a home visit was associated with readmission (with any condition, not just complicated SAM) and death, as previously published (Berkley et al, ; Ngari et al, a).…”
Section: Methodssupporting
confidence: 69%
“…The goal of SAM treatment also includes the reduction of susceptibility to life‐threatening infections, restoration of a healthy body composition, and improvement in neurocognitive status (Ngari et al, a). However, children with SAM remain at risk of developing severe illness and/or infections after treatment of clinical complications and discharged from hospital (Berkley et al, ; Chisti et al, ; Kerac et al, ; Ngari et al, a). A study by Kerac et al () that followed 1,024 children 1 year post‐discharge reported 5% hospital readmissions but 42% deaths, whereas Khanum et al () reported 1.2% emergency hospital readmissions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…106 Second, among 1778 children who had recovered from severe acute undernutrition in one of four Kenyan hospitals, six months of oral co-trimoxazole (120 mg/day if <6 months of age; 240 mg/day if >6 months) had no effect on mortality during the 12-month study period. 107 It is possible that the beneficial effect on growth observed in the Malawian trial resulted from microbiota restructuring. However, the cohort of 64 undernourished Bangladeshi children studied by Subramanian et al exhibited only a transient restoration of gut microbiota maturity that was lost four months after inpatient treatment.…”
Section: Microbiome-targeting Therapies Have Thus Far Demonstrated LImentioning
confidence: 99%